Biodiversity of the termite (isoptera) fauna in crop environments - Jyothy Narayanan (Department of Agricultural Entomology, College of Horticulture, 2011)
Termites (Insecta: Isoptera) are eusocial insects living in a highly organised and small to large extent of communities in different ecosystems. A termite colony has morphologically and functionally distinct caste system which includes functional reproductives / ‘royal pair’ of king and queen, sterile soldier and worker castes and the immature stages or nymphs along with other inquiline species of organisms. The present investigation on the ‘Biodiversity of the termite (Isoptera) fauna in crop environments’ was undertaken in a few selected crop environments in the instructional farm area of the College of Horticulture at Vellanikkara during 2010-11. The main objectives of the study were to identify the composition of the termite fauna up to the family/ genus level in mango, cashew, cocoa and coconut crop environments, elucidation of their feeding nature, behaviour, association and their mound forming characteristics and to prepare a primary termite colonisation map in the selected plantation and orchard systems in this tract. A preliminary survey was conducted by transect walk throughout the instructional farm area of the campus to select the termite prone plantation and orchard systems for the study. The soldier castes of termites were sampled from a unit area of 200 sq. m each from different crop environments and kept under preservation. The soldier castes from earthen mounds were collected by a special “Glue trap technique” designed and standardised for the purpose by the author through 20 numbers of encounter samplings per unit area of observation. The soldier castes were identified based on the standard keys (Bose, 1984; Roonwal and Chhotani, 1961 and Sornnuwat et al., 2004) with reference to their characteristics of head capsule, mandibles and pronotum. The diversity pattern of termite genera in different agro ecosystems in Vellanikkara were assessed by using various diversity indices. Based on these information, a preliminary termite colonisation map was prepared by depicting the distribution, spread and colonisation density of the identified termite genera in the selected crop environments. The morphometry of the aerial mounds along with some of the physical properties of the termitarial soils were also determined. The influence of temperature and humidity on the termite colonisation process was also observed. A total of nine termite genera under two families were identified in Vellanikkara. Out of this, seven termite genera viz., Odontotermes, Procapritermes, Dicuspiditermes, Homallotermes, Microtermes, Microcerotermes and Nasutitermes were under the family Termitidae, while, Heterotermes and Coptotermes were coming under the family Rhinotermitidae. Odontotermes was found to be the most dominant genus in all the selected crop environments accounting for about 62.03 per cent of the total genera identified from the Vellanikkara tract. The least present genus was Coptotermes which constituted only 1.27 per cent among all the identified genera. Based on the distribution, spread and colonisation density, a primary termite faunal distribution map was prepared in selected systems. The genera viz., Odontotermes, Microcerotermes, Nasutitermes, Heterotermes and Coptotermes were identified as wood feeders while, Procapritermes, Dicuspiditermes, Homallotermes and Microtermes were observed as soil/ humus feeders. Various diversity indices were worked out for the faunal distribution of the termites in this tract to find out their relative dominance, spread and evenness in its distribution. The genus richness of the termite genera at Vellanikkara tract was found to be 9 and the value of Simpson- Yule diversity Index (D) was found to be 2.44 and that of the Shannon- Weiner Diversity Index (H) was found to be 1.38. The Evenness Index (E) when worked out was found to be 0.63 and the Berger Parker Dominance Index (d) for the genus Odontotermes was found to be 0.62. When different systems were compared, the genus richness was found to be the highest in cashew plantation with a value of 6 while, the mango, cocoa and coconut systems were having a value of 3 only. The D value of 4.65, H value of 1.64 and the E value of 0.92 was found to be highest in cashew plantation, which indicated that the cashew system was supporting maximum generic diversity of the termites with a more evenness in its distribution. The values of these indices were found to be the lowest in cocoa which indicated that the cocoa based systems was having the lowest diversity and very low evenness in the distribution of various genera. The mango and coconut based systems were having intermediate values with these indices. The “d” value indicating the dominance of the particular termite genus viz., Odontotermes was found to be the highest in the cocoa based system with a value of 0.75 and the least in cashew with a value of 0.33. The mean density of the mounds in mango, cashew and cocoa based systems varied only slightly indicating their relative uniform distribution. The mean number of buttresses or young mounds ranged from 5- 7 per mound formation. The mean height of the mounds present in all the three systems showed only very slight variation, but there was difference in the mean basal circumference of the mounds in the three systems. Accordingly, the mean external volume (above ground) of the mounds in cubic centimetres was found to be the highest in cocoa and least in mango based systems. Statistical analysis of the data revealed that there was no significant difference in the relative per cent increase in the external volume of the mounds in cocoa plantation, while, there was significant difference in the change of volume as observed in July’10- Aug’10 and Jan’11- Feb’11 in mango and cashew based systems implicating the degree and period of termite activity within the termitaria. Regarding the physical properties, the soil colour of the mounds and of the adjacent soil during the wet season was found to be dark reddish brown as per the visual comparison through the standard Munsell colour chart. However, the colour of the mound soil and of the adjacent soil during the dry season was found to be brown and dark reddish brown, respectively. Particle size distribution in the soil samples of the termitarial mounds from the three crop environments viz., mango, cashew and cocoa based systems showed no significant difference among them. But within the same crop systems, the clay content of the mound soil was observed to be increasing by 10-12 per cent while, the sand content was decreasing by about 10-15 per cent. There was not much variation in silt content between the mound soil and adjacent soil. However, gravel was found to be totally absent in the mound soil as compared to the adjacent soils. When the temperature and relative humidity were recorded and compared between inside and outside of the mounds, it was found out that both temperature and relative humidity inside the mounds were significantly higher than that of the external environment which prove that the termites have to essentially maintain their homoeostasis with respect to the internal ambience for their survival and other activities irrespective of the external ambience. To conclude, the study reveals that the Vellanikkara tract is diverse in the faunal distribution of termites with nine genera under two families and five subfamilies with a dominant mound dwelling genus viz., Odontotermes in all the crop environments of mango, cashew, cocoa and coconut systems. The identification of the termite genera can very well be undertaken based on head capsule and mandibular characteristics of the soldier caste by collecting them easily by the newly designed method of “glue trap technique” by the author. The termites colonize these systems without any major environmental or resource degradation and thereby their role may be further investigated for the eco restoration and conservation activities.